2016
DOI: 10.1186/s12943-016-0551-1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of T helper 17 and regulatory T cells in lung cancer progression and metastasis

Abstract: Lung cancer is a leading cause of cancer-related deaths worldwide. Lung cancer risk factors, including smoking and exposure to environmental carcinogens, have been linked to chronic inflammation. An integral feature of inflammation is the activation, expansion and infiltration of diverse immune cell types, including CD4+ T cells. Within this T cell subset are immunosuppressive regulatory T (Treg) cells and pro-inflammatory T helper 17 (Th17) cells that act in a fine balance to regulate appropriate adaptive imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(128 citation statements)
references
References 163 publications
(146 reference statements)
3
122
0
Order By: Relevance
“…The Treg/Th17 balance plays a key role in maintaining the stability of the immune state [9, 10]. An imbalance can cause a series of immune inflammatory responses that are characteristic of cancer, autoimmune diseases, atherosclerosis, allergic asthma and diseases of the development process [11-15]. Clinical studies have found that the presence of Treg cells in patients undergoing dialysis for end-stage renal failure significantly reduced the frequency of cellular and functional damage and significantly increased the Th17 cell frequency [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Treg/Th17 balance plays a key role in maintaining the stability of the immune state [9, 10]. An imbalance can cause a series of immune inflammatory responses that are characteristic of cancer, autoimmune diseases, atherosclerosis, allergic asthma and diseases of the development process [11-15]. Clinical studies have found that the presence of Treg cells in patients undergoing dialysis for end-stage renal failure significantly reduced the frequency of cellular and functional damage and significantly increased the Th17 cell frequency [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancers (LC) are the leading cause of deaths from cancer (1)(2)(3)(4). FOXP3 + Tregs are thought to facilitate tumor growth and metastases by inhibition of antitumor immunity (5)(6)(7)(8), and accumulation of Tregs within cancers usually corresponds with poor outcomes (4,6,9), although exceptions are known (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…FOXP3 + Tregs are thought to facilitate tumor growth and metastases by inhibition of antitumor immunity (5)(6)(7)(8), and accumulation of Tregs within cancers usually corresponds with poor outcomes (4,6,9), although exceptions are known (10)(11)(12). These inconsistencies suggest that mere enumeration of tumor-infiltrating FOXP3 + cells may not be sufficiently incisive for understanding the biology of Tregs in clinical oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of plasma cell markers were also found to be increased in tumour samples compared to normal (FC = 2.87) (Figure 1A). While Tregs and M0 macrophages have been extensively described in lung cancer, 18,19 Tfh cells remains relatively understudied.
10.1080/2162402X.2018.1504728-F0001Figure 1. Relative expression of immune cell subsets in bulk gene expression data . A) CIBERSORT was used to deconvolve cell fractions of 22 immune cell subsets in matched tumour (n = 83) and normal (n = 83) samples, and the tumour to normal ratio of each cell type was calculated per each matched pair and the mean across the cohort calculated.
…”
Section: Resultsmentioning
confidence: 99%